Costs and outcomes evaluation of patient navigation after abnormal cancer screening: Evidence from the Patient Navigation Research Program. Issue 4 (25th October 2013) - Bensink, Mark E.; Ramsey, Scott D.; Battaglia, Tracy; Fiscella, Kevin; Hurd, Thelma C.; McKoy, June M.; Patierno, Steven R.; Raich, Peter C.; Seiber, Eric E.; Warren‐Mears, Victoria; Whitley, Elizabeth; Paskett, Electra D.; et al.
Abstract : BACKGROUND: Navigators can facilitate timely access to cancer services, but to the authors' knowledge there are little data available regarding their economic impact. METHODS: The authors conducted a cost‐consequence analysis of navigation versus usual care among 10, 521 individuals with abnormal breast, cervical, colorectal, or prostate cancer screening results who enrolled in the Patient Navigation Research Program study from January 1, 2006 to March 31, 2010. Navigation costs included diagnostic evaluation, patient and staff time, materials, and overhead. Consequences or outcomes were time to diagnostic resolution and probability of resolution. Differences in costs and outcomes were evaluated using multilevel, mixed‐effects regression modeling adjusting for age, race/ethnicity, language, marital status, insurance status, cancer, and site clustering. RESULTS: The majority of individuals were members of a minority (70.7%) and uninsured or publically insured (72.7%). Diagnostic resolution was higher for navigation versus usual care at 180 days (56.2% vs 53.8%; P = .008) and 270 days (70.0% vs 68.2%; P < .001). Although there were no differences in the average number of days to resolution between the 2 groups (110 days vs 109 days; P = .63), the probability of ever having diagnostic resolution was higher for the navigation group versus the usual‐care group (84.5% vs 79.6%; P < .001). The added cost of navigation versus usual care was 275 per patient (95% confidence interval, 260‐290; P < .001). There was no significant difference in stage distribution among the 12.4% of patients in the navigation group vs 11% of the usual‐care patients diagnosed with cancer. CONCLUSIONS: Navigation adds costs and modestly increases the probability of diagnostic resolution among patients with abnormal screening test results. Navigation is only likely to be cost‐effective if improved resolution translates into an earlier cancer stage at the time of diagnosis. Cancer 2014;120:570–578 . © 2013 American Cancer Society . Abstract : Patient navigation adds costs to screening programs and modestly increases the probability of diagnostic resolution. The navigation of patients with abnormal results from screening for breast, colorectal, cervical, and prostate cancer is only likely to be cost‐effective if increases in resolution translate into the detection of earlier cancer stage at diagnosis.